2016
DOI: 10.1007/s12253-016-0154-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive DNA Methylation and Mutation Analyses Reveal a Methylation Signature in Colorectal Sessile Serrated Adenomas

Abstract: Colorectal sessile serrated adenomas (SSA) are hypothesized to be precursor lesions of an alternative, serrated pathway of colorectal cancer, abundant in genes with aberrant promoter DNA hypermethylation. In our present pilot study, we explored DNA methylation profiles and examined selected gene mutations in SSA. Biopsy samples from patients undergoing screening colonoscopy were obtained during endoscopic examination. After DNA isolation and quality analysis, SSAs (n = 4) and healthy controls (n = 5) were chos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…In our study, we found a lower frequency of APC (41.8%) and CTNNB1 (3.3%) mutations, which can be because we did not analyze the whole coding sequence, but the major hotspot regions of both genes. In the serrated polyps pathway, the WNT signaling is reported to be less targeted 27,33 , following our ndings.…”
Section: Discussionsupporting
confidence: 76%
“…In our study, we found a lower frequency of APC (41.8%) and CTNNB1 (3.3%) mutations, which can be because we did not analyze the whole coding sequence, but the major hotspot regions of both genes. In the serrated polyps pathway, the WNT signaling is reported to be less targeted 27,33 , following our ndings.…”
Section: Discussionsupporting
confidence: 76%
“…Likely as a result of this observed hypermethylation in CRC, the SST mRNA level was decreased in CRC compared to normal tissue, as demonstrated with microarray data [93]. In a small pilot study with only 4 samples collected from patients with pre-neoplastic colorectal sessile serrated adenomas, SST hypermethylation was demonstrated in all examined patients [94]. These results indicate that, among others, the downregulation of SST may be involved in the development of CRC.…”
Section: Epigenetic Regulation Of Sst In Cancersupporting
confidence: 52%
“…Since neurokinin A inhibits cell proliferation in normal cell (37), TAC1 is therefore considered a tumor-suppressor gene, and hypermethylation of the TAC1 CpG island promoter has been observed in various types of cancer, including lung (non-small cell type) cancer (14), colon cancer (15), head and neck cancer (16), uterus cancer (17) and pancreatic cancer (27,28). Patai et al (38) reported that TAC1 promoter is hypermethylated in the precancerous condition of colorectal sessile serrated adenomas. Subsequently, TAC1 gene methylation is likely to occur during the early stage of tumorigenesis in colorectal cancer (38).…”
Section: Discussionmentioning
confidence: 99%
“…Patai et al (38) reported that TAC1 promoter is hypermethylated in the precancerous condition of colorectal sessile serrated adenomas. Subsequently, TAC1 gene methylation is likely to occur during the early stage of tumorigenesis in colorectal cancer (38). In the present study, TAC1 promoter methylation was higher in pancreatic cancer tissues compared with that in adjacent non-cancerous tissues.…”
Section: Discussionmentioning
confidence: 99%